Chromosomal evolution in the pallescens group (Hemiptera, Triatominae) - Alevi, K. C. C. [UNESP]; Ravazi, A. [UNESP]; Franco-Bernardes, M. F. [UNESP]; Rosa, J. A. [UNESP]; Azeredo-Oliveira, M. T. V. [UNESP] (Funpec-editora, 2015)
Rhodnius colombiensis, in conjunction with R. pallescens and R. ecuadoriensis, forms the monophyletic pallescens group. Cytogenetic analyses of these closely related species would further our understanding of the taxonomy and evolution of this group. In this study, R. colombiensis was cytogenetically analyzed, and the results were compared with cytogenetic data from other species of the pallescens group, particularly their chromosomal evolution. We found that this triatomine has heteropycnotic blocks in five autosomal bivalents at both metaphase I and II. The derivation of R. colombiensis from R. pallescens led to significant loss of heteropycnotic and heterochromatic regions (approximately 50%). R. ecuadoriensis is the most differentiated of the group because it has lost all heterochromatin and heteropyknotic blocks in the autosomes. Based on the heteropyknotic and heterochromatic pattern of R. colombiensis and the chromosomal evolution analysis of the pallescens group, we suggest that the karyotype of R. colombiensis and R. ecuadoriensis lost its heteropycnotic and heterochromatic blocks during speciation. Furthermore, this loss could be related to adaptation to different environments.
Keywords: Rhodnius colombiensis; Tribe Rhodniini; Cytogenetic